Computation of equilibrium measures - Olver, S (Unspecified, 2010)
We present a new way of computing equilibrium measures, based on the Riemann-Hilbert formulation. For equilibrium measures whose support is a single interval, the simple algorithm consists of a Newton-Raphson iteration where each step only involves fast cosine transforms. The approach is then generalized for multiple intervals.